Content distribution to segmented audiences: platforms and the crowd concept. : Study case: Infinito+1 - Fernández Manzano, Eva Patricia; Linares Palomar, Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article aims to analyze how the new distribution windows interrupt the distribution of audiovisual content. For this, the case of the production company Infinito+1 is studied when approaching a specific segment of the audience: the religious community. The behavior of this type of so-called niche audience offers a diversity of possibilities within content distribution, such as crowdfunding, crowdsourcing or platform on demand. These actions will be analyzed and studied with the idea of understanding the actuality of the audiences and the distribution of content.